PERANCANGAN WEBSITE INFORMASI PENYEWAAN ALAT OUTDOOR HIKING (STUDI KASUS CERITA OUTDOOR MAJALENGKA) - Cesoria, Yola Zerlinda; Bastian, Ade (Universitas Majalengka, 2025)
This research aims to develop a Web-based Information System for Outdoor Hiking Equipment Rental at Cerita Outdoor Majalengka. The study addresses challenges in manual processes, including stock management errors, inefficient data recording, and reliance on WhatsApp communication. Using the Laravel framework and the Waterfall method, the system was designed to optimize stock and transaction management while improving customer convenience. The website allows users to register, log in, browse products with details, and place rental orders by selecting dates and durations. Payments are supported via bank transfer and confirmed by the admin. Meanwhile, admins can manage stock, monitor transactions, and access real-time records more efficiently. The system also supports structured transaction documentation, reducing errors and saving time. Test results show that the system successfully simplifies operations, enhances data accuracy, and increases customer satisfaction by providing a faster and more reliable rental service.